Complications Associated with the Use of Supraglottic Airway Devices in Perioperative Medicine - Michalek, Pavel; Donaldson, William; Vobrubova, Eliska; Hakl, Marek (BioMed research international, 2015)
Supraglottic airway devices are routinely used for airway maintenance in elective surgical procedures where aspiration is not a significant risk and also as rescue devices in difficult airway management. Some devices now have features mitigating risk of aspiration, such as drain tubes or compartments to manage regurgitated content. Despite this, the use of these device may be associated with various complications including aspiration. This review highlights the types and incidence of these complications. They include regurgitation and aspiration of gastric contents, compression of vascular structures, trauma, and nerve injury. The incidence of such complications is quite low, but as some carry with them a significant degree of morbidity the need to follow manufacturers' advice is underlined. The incidence of gastric content aspiration associated with the devices is estimated to be as low as 0.02% with perioperative regurgitation being significantly higher but underreported. Other serious, but extremely rare, complications include pharyngeal rupture, pneumomediastinum, mediastinitis, or arytenoid dislocation. Mild short-lasting adverse effects of the devices have significantly higher incidence than serious complications and involve postoperative sore throat, dysphagia, pain on swallowing, or hoarseness. Devices may have deleterious effect on cervical mucosa or vasculature depending on their cuff volume and pressure.
Keywords: Pharynx; zajištění dýchacích cest; extubace; faryngitida; Perioperative Period; Airway Management; poruchy polykání; perioperační období; Pharyngitis; Postoperative Complications; lidé; Airway Extubation; pooperační komplikace; farynx; Elective Surgical Procedures; Deglutition Disorders; Humans; elektivní chirurgické výkony